Comparative transcriptomes reveal pro-survival and cytotoxic programs of mucosal-associated invariant T cells upon Bacillus Calmette–Guérin stimulation - Sharma, Manju; Niu, Liang; Zhang, Xiang; Huang, Shouxiong (Frontiers in Cellular and Infection Microbiology, 2023)
Mucosal-associated invariant T (MAIT) cells are protective against tuberculous and non-tuberculous mycobacterial infections with poorly understood mechanisms. Despite an innate-like nature, MAIT cell responses remain heterogeneous in bacterial infections. To comprehensively characterize MAIT activation programs responding to different bacteria, we stimulated MAIT cells with E. coli to compare with Bacillus Calmette-Guérin (BCG), which remains the only licensed vaccine and a feasible tool for investigating anti-mycobacterial immunity in humans. Upon sequencing mRNA from the activated and inactivated CD8+ MAIT cells, results demonstrated the altered MAIT cell gene profiles by each bacterium with upregulated expression of activation markers, transcription factors, cytokines, and cytolytic mediators crucial in anti-mycobacterial responses. Compared with E. coli, BCG altered more MAIT cell genes to enhance cell survival and cytolysis. Flow cytometry analyses similarly displayed a more upregulated protein expression of B-cell lymphoma 2 and T-box transcription factor Eomesodermin in BCG compared to E.coli stimulations. Thus, the transcriptomic program and protein expression of MAIT cells together displayed enhanced pro-survival and cytotoxic programs in response to BCG stimulation, supporting BCG induces cell-mediated effector responses of MAIT cells to fight mycobacterial infections.